Co and Zn Metal Phthalocyanines with Bulky Substituents: Anticancer, Antibacterial Activities and Their Inhibitory Effects on Some Metabolic Enzymes with Molecular Docking Studies - Turkan, Fikret; Taslimi, Parham; Cabir, Beyza; Agirtas, Mehmet Salih; Erden, Yavuz; Celebioglu, Hasan Ufuk; Tuzun, Burak (Taylor & Francis Ltd, 2021)
In this study, we reported the synthesis of new cobalt and zinc phthalocyanine compounds with ((ethylenediamine-N,N',N'-triacetic acid-N-2-ethyl)oxy) (ETAEO) substituted groups. Characterization studies and anticancer properties of both synthesized compounds were determined as well. The inhibitory effects of these complexes on some metabolic enzymes were examined and it was observed that the enzymes inhibited by complex molecules at the micromolar levels. In addition, the active sites of the enzymes were determined by molecular modeling programme for screening the enzyme-inhibitor interactions. The molecular docking method was used to calculate the interactions of molecules with enzymes. Also, human prostate and breast cancer cell lines (PC-3 and MCF-7) were used to determine the anticancer properties of the complexes. All doses of the tetrakis (ETAEO) phthalocyaninato Cobalt II (1) did not show any significant changes in PC-3 cell viability, but significantly reduced in MCF-7 cell viability. Similarly, all doses of the tetrakis (ETAEO) phthalocyaninato zinc II (2) significantly reduced MCF-7 cell viability compared to the control and solvent control groups. According to the enzyme inhibition studies, both complexes showed the best inhibition effects for alpha-Glycosidase enzyme with 125.85 +/- 30.35 mu M and 165.30 +/- 27.18 mu M Ki values.
Keywords: Phthalocyanine; antibacterial; anticancer; enzyme inhibition; molecular docking